THE USE OF INTERACTIVE STUDYING METHODS IN TEACHING OPERATIVE SURGERY AND TOPOGRAPHIC ANATOMY - V.M. Fedorak (Український стоматологічний альманах, 2015)
One of the main requirements of credit-modular system of studying at medical schools is improving the quality of training of future doctors, because patients' lives depend on their knowledge and skills. That’s why the department along with traditional methods is using new teaching methods. It is very important for the balance to be observed between theoretical knowledge with practical skills and operational technique.